THE REASON OF STUDENTS’ RETICENCE IN AN EFL CLASS - Gunawan, Iyong Yoga; Sada, Clarry; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Oral participation is inherently important in English classroom. The writer observed and found that the grade VIII students of SMP LKIA Pontianak, tended to be reticent when classroom discussion conducted. They chose to remain silent rather than participating actively in the discussion. This study aimed to investigate the reasons for students’ reticence in English classroom using case study method. The participants were three students from Class VIII of SMP LKIA Pontianak. The participants were chosen by the characteristics of reticence such as tending to be reluctant in responding teachers’ or other students’ questions, sitting at the middle/back rows, and rarely asking questions (rarely raising hand). Using direct observation and semi-structured interview, the study found that the main reasons of students’ reticence were anxiety, shyness, unfamiliarity with the topics/materials, low English proficiency, fear of making mistakes, lacking confidence in oneself, and being underprepared. Based on the findings, it showed that affective, individual, and psychological factors had a dominant influence on students’ reticence. Keywords: EFL Class, Students’ Reticence, Reasons..